Population age structural transition, demographic dividend and economic growth in India - Neha Jain; Srinivas Goli; Arjun Jana (Humanities & Social Sciences Communications)
Abstract In this paper, we have estimated India’s demographic dividend (i.e. macroeconomic return to demographic transition) by human capital approach and macro-economic regression models considering a longer and more appropriate time frame compared to previous studies and also modelled interaction analyses that purport to explain the mechanisms under which dividends are realised and also to understand the context they are expected to be largest. Our main analysis using panel data regressions highlights three key points. First, the demographic dividend is estimated to be about 1.9 percentage points per annum for the period 1981–2021 after controlling for core policy variables. Second, the favourable economic impact of demographic transition strengthened after 2011 but withered away in 2020–21 due to the Covid-19 pandemic. Third, the results based on interaction models support the argument that the realisation of the demographic dividend is conditional on a conducive policy environment with enabling aspects such as good healthcare, decent employment opportunities, and gender empowerment. The robustness of the main findings is verified by correcting for endogeneity using the instrumental variable regression model. Further, we validated our results by comparing our estimates based on the conditional Barro-regression model with previous studies.